Current principles and practice in autologous intraportal islet transplantation: a meta‐analysis of the technical considerations. Issue 4 (14th March 2016) - Kumar, Rohan; Chung, Wen Yuan; Dennison, Ashley Robert; Garcea, Giuseppe
Abstract: Objectives: Autologous islet transplantation (IAT) following pancreatectomy is now a recognized, albeit highly specialized procedure carried out in a small number of centers worldwide. Current clinical principles and best practice with emphasis on examining the technical aspects of surgery in centers with significant IAT experience are reviewed. Methods: Literature search for studies discussing any technical aspect of pancreatectomy with intraportal IAT was included. Results: Thirty‐five papers were included; all were single‐center case series. The indications, surgical approach to pancreatectomy with IAT, islet yield, static pancreas preservation prior to islet digestion, portal vein access, absolute islet infusion volumes, and portal venous pressure changes during transfusion evaluated. Conclusions: IAT is considered a "last resort" when alternative approaches have been exhausted. Pre‐morbid histology and prior surgical drainage adversely influence islet yields and may influence the clinical decision to perform pancreatectomy and IAT. Following pancreas digestion, absolute numbers of islets recovered and smaller islet size predict rates of insulin independence following IAT. Islet volumes and portal venous pressure changes are important factors for the development of complications. Surgical access for IAT includes intra‐operative, immediate or delayed infusion via an "exteriorized" vein, and radiological percutaneous approaches. Delayed infusion can be combined with pancreas preservation techniques prior to islet isolation.